Burn wounds in the young versus the aged patient display differential immunological responses. Issue 6 (September 2018) - Farinas, Angel F.; Bamba, Ravinder; Pollins, Alonda C.; Cardwell, Nancy L.; Nanney, Lillian B.; Thayer, Wesley P.
Highlights: Immunological differences at point of injury between young and elderly burn patients. EGF & CCF (RANTES) are significantly elevated locally in younger burn patient wounds. Increased wound macrophage concentration in younger burn patients. Abstract: Background: Individuals in the geriatric age range are more prone than younger individuals to convert their partial thickness thermal burns into full thickness injuries. We hypothesized that this often observed clinical phenomenon is strongly related to differential local injury responses mediated by the immune system. Materials & methods: Skin samples from areas with partial thickness thermal burns were obtained during routine excision and grafting procedures between post burn days 2–6. Tissue samples were grouped by age ranges with young patients defined as <30 years of age or aged patients defined as >65. Formalin fixed samples were used to confirm depth of burn injury and companion sections were homogenized for multiplex analysis using a Luminex platform. Immunohistochemical staining was used to quantify total macrophage numbers as well as the M1 and M2 subpopulations. Results: Our analysis includes samples derived from 11 young subjects (mean age = 23) and 3 aged subjects (mean age = 79.2). Our initial survey of analytes examined 31 cytokines/chemokines. Twelve were excluded from consideration as they were present in concentrations either above or below the optimal detection range. Two analytes emerged as candidate molecules with significant differences between the young and the aged patient responses to burn injury. EGF levels were on average 21.69 pg/ml in young vs 14.87 pg/ml in aged (p = 0.032). RANTES/CCL5 levels were on average 14.86 pg/ml in young vs 4.26 pg/ml in aged (p = 0.026). Elevated macrophage numbers were present within wounds of younger patients compared to the old (p < 0.01), with a higher concentration of the M1 type in the elderly (p > 0.05). Conclusion: Our study has identified at least 2 well known cytokines, CCL5 (RANTES) and EGF, which are differentially regulated in response to burn injury by young versus aged burn victims. Evidence suggests that a proinflammatory environment can explain the high conversion rate from partial to full thickness burns. Our data suggest the need for future studies at the point of injury (cutaneous targets) that may be modulated by post burn release of cytokines/chemokines.